PENGEMBANGAN MODUL SIFAT KEPERIODIKAN UNSUR BERBASIS GUIDED DISCOVERY LEARNING UNTUK KELAS X SMA - Murdiati, Vivin (Journal of Technique Research (JTR), 2019)
This research is aimed to develop the module of periodic nature of the element on  guided discovery learning. The type of research used is research and development or Research and Development (R&D). The development model used is Plomp model which consists of 3 stages, namely: preliminary research, prototyping satge, and assessment phase. The validity test of this module was done by 2 lectures at FMIPA UNP, 2 chemistry teachers at SMAN 3 Padang Panjang and 1 chemistry teachers at SMA Pembangunan Laboratorium UNP using validation instrument. Practicality test was done by 2 chemistry teachers at SMAN 3 Padang Panjang and 29 student X MIPA 1 of SMAN 3 Padang Panjang using practical questionnaires. Validity instrument and practical questionnaires was analyzed using the Cohen Kappa (k) formula. The results of the validity test showed that the module has a very high validity category (k = 0,89). Practicality test results by teachers and students showed that the module has high practicality category (k = 0,90 and 0,84). Based on the results of this research, it can be concluded that the module of periodic nature of the element on guided discovery learning was produced for valid and practical high school students.